AKIBAT HUKUM PENOLAKAN PERMOHONAN ITSBAT NIKAH OLEH PENGADILAN AGAMA TERHADAP PARA PIHAK YANG MELAKUKAN NIKAH SIRI (STUDI KASUS PUTUSAN NOMOR: 1478/Pdt.G/2016/PAJT) - Hafidz Nugroho; Imelda Martinelli (Jurnal Hukum Adigama, 2018)
Siri marriage is marriage opposed to the act of mating because it is not registered, usually siri marriage used by the husband to have more than one wife, basically nikah siri do not have the force of law and not guarantee the rights of a wife and child,  for that entreaty itsbat marriage to the religious court to help the parties husband and wife to get marriage certificate, so that it will have the force of law and guarantee the rights of a wife and chil, but the submission of itsbat nikah rejected by religious court by reason of the husband did not ask for permission wife in the past and the court, how did due to the law of renuncation itsbat nikah ?  the author examines these issues with normative juridical analysis. The data were drawn in the ruling writer analyzes that it is has no permit wife in the past and also the court, Resulting in refusal entreaty the itsbat marriage, Its impact is against marital status to be illegitimate in the state,  and the status of a child to be children outside of mating. The government should supervise and socialize about the  siri marriage and Due to everything that can be inflicted